β-catenin links cell seeding density to global gene expression during mouse embryonic stem cell differentiation - Lucy LeBlanc; Mijeong Kim; Aparna Kambhampati; Albert J. Son; Nereida Ramirez; Jonghwan Kim (iScience, 2022)
Summary: Although cell density is known to affect numerous biological processes including gene expression and cell fate specification, mechanistic understanding of what factors link cell density to global gene regulation is lacking. Here, we reveal that the expression of thousands of genes in mouse embryonic stem cells (mESCs) is affected by cell seeding density and that low cell density enhances the efficiency of differentiation. Mechanistically, β-catenin is localized primarily to adherens junctions during both self-renewal and differentiation at high density. However, when mESCs differentiate at low density, β-catenin translocates to the nucleus and associates with Tcf7l1, inducing co-occupied lineage markers. Meanwhile, Esrrb sustains the expression of pluripotency-associated genes while repressing lineage markers at high density, and its association with DNA decreases at low density. Our results provide new insights into the previously neglected but pervasive phenomenon of density-dependent gene regulation.